Maximizing the potential of water buffalo milkability: best practices and lessons learned - Carlo Boselli; Antonio Borghese (Revista Científica)
Milk yield and flow profiles are essential parameters to record and evaluate. Buffaloes are characterized by longer teats and teat canals and, in particular, stronger muscular resistance of the teat wall than in cows; it is necessary to have a high vacuum level to open the teat canal and begin milk ejection. The milk stored in the buffalo udder can be divided into two fractions: the cisternal fraction, which has already been transferred from the alveoli to the cistern during the interval between milkings and is immediately available, and the alveolar fraction, which can only be removed from the udder by the action of oxytocin. In buffalo milking management, the milking machine is a critical point, and the characteristics of the milking vacuum and the pulsation rate are closely related to milk flow observations; in Italy, the most commonly used vacuum levels are 44–46 kPa (range 40–53 kPa). The data on the milkability traits of the Mediterranean Italian breed made it possible to classify eight different types of milk flow curves due to anatomical, physiological, and management differences. The most represented milk flow curve was type 3 (with a similar time between PPT and DPT, 27.32%), followed by type 6 (17.79%), characterized by a very long plateau phase. The least represented curve was type 1 (4.41%), characterized by a long lag time and low peak flow rate. Buffaloes with curves of type 5 (10.62%) and 6 (17.79%) were characterized by the highest milk yield at milking, the lowest somatic cell score, and the shortest milking time. The analysis of the milk emission profiles showed an excessive duration of DPT and overmilking (BT); these results suggest the detachment of the milking cluster to reduce the BT with the following advantages: a) reduction of the total milking time and consequently of the worker’s time, b) improvement of the farmer’s income and milk quality thought the mastitis incidence decreases. Concerning the automation of milking technologies, a recent study analyzed the main milk flow traits and milk yield recorded in Mediterranean Italian buffaloes milked with the Automatic Milking System (AMS). The results showed a considerable variation in milk ejection and, consequently, in the milk flow curves of the buffaloes milked in AMS with a forced system compared to the conventional one. The differences were the following: better pre-stimulation allowing a positive endogenous release of oxytocin, with reduced lag time; independent milk ejection for each teat, with optimal milking of all quarters, with the reduction of BT; improvement of milking hygiene during milking, limiting the incidence of mastitis and with a low value of somatic cell score; adverse effects due to failed or incomplete milking (17% of the total milkings), limiting the potential capacity and efficiency of AMS; frequent leakage of airflow, which could cause alteration of milk composition. In conclusion, continuous monitoring of milk ability will help to optimize milking practices by reducing labor time and increasing farmers’ income through better milk quality and fewer udder issues. In addition, the identification of buffaloes with desirable types of milk flow curves could be helpful for buffalo breeders’ associations to address farmer management and also to define potential new breeding objectives.